Developing L2 Learners Metacognitive Strategies through Reading Group Activities - Loppies, Hellien J.; Lekatompessy, Jeny (Huele: Journal of Applied Linguistics, Literature and Culture, 2021)
The trend of teaching reading comprehension has shifted the gear from cognitive development to metacognitive orientation and Reading Group activity is one way to foster knowledge constructions and meaning-making in the scheme of metacognition. Reviewing the theoretical foundations of reading group activities, this article theoretically addresses how a reading group can promote individual L2 readers' metacognitive reading strategies. This article emphasizes the importance of implementing a reading group to support second language readers to self-regulate their metacognitive reading strategies by planning, monitoring, and evaluating an academic reading text. Further, this article elaborates on adapting principles in setting up reading group activities, based on the authors' L2 teaching practices. Finally, recommendations and directions for future studies are also provided.